Performance test method of composite structure laser ceramic
By testing the physical and chemical characteristics and laser output characteristics of composite structure laser ceramics, the problem of difficulty in effectively testing the performance of composite structure laser ceramics in the existing technology is solved, and a comprehensive evaluation and optimization of the performance of laser ceramics is achieved, providing an effective testing method for high-performance lasers.
Patent Information
- Application Number
- CN202411684641.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-11-22
AI Technical Summary
The prior art is difficult to effectively test the performance of composite structure laser ceramics, resulting in the laser output efficiency, beam quality and output power stability.
A performance testing method for composite structure laser ceramics is proposed, including physical and chemical characteristics testing and laser output characteristics testing. Physical and chemical characteristics tests include ceramic density test, microstructure test, transmittance test, stress test and ion doping test; laser output characteristics tests include pump light absorption characteristic test, thermal lens focal length test, end surface temperature test and laser output power test.
Through this test method, the comprehensive performance of composite structure laser ceramics can be effectively evaluated, provided strong support for the preparation of high-performance composite structure laser ceramics, and improved the performance and production efficiency of the laser.
Smart Images

Figure CN119643835A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of performance testing of composite structure laser ceramics, and in particular to a performance testing method of composite structure laser ceramics. Background Art
[0002] With the maturity of ground equipment, many applications have expanded their scope to the fields of astronomy and space, such as quantum communication, space gravitational wave detection, deep space communication, etc., which puts higher requirements on the performance of high-power single-frequency continuous lasers. In addition to high beam quality, high power, and narrow linewidth output, the laser is also required to have long life, low energy consumption, and radiation resistance. When using traditional uniformly doped Nd:YAG and Nd:YVO4 crystals as gain media, under high-power pumping, the early absorption of the pump laser by the doped ions at the incident end of the crystal causes the absorption of the pump laser to weaken at the middle and back ends of the crystal, thereby causing uneven heat distribution inside the crystal along the direction of laser propagation. The temperature gradient caused by uneven heat distribution produces a serious thermal lens effect inside the crystal, which will greatly reduce the laser light output efficiency, beam quality, and output power stability.
[0003] Although laser ceramics as laser gain media have attractive prospects, their preparation process is full of challenges. As early as 1995, Dr. Ikesue of Japan achieved the preparation of low scattering loss Nd:YAG laser ceramics through vacuum reaction sintering technology and realized laser output for the first time. This research has also attracted widespread attention from scholars in related fields around the world. In 2001, Konoshima Company of Japan successfully achieved small-scale preparation of YAG-based laser ceramics, and its scattering loss reached 0.001cm -1level, and the process of practical application and productization has accelerated. In 2002, with the support of the US Air Force project, VLOC conducted a systematic evaluation of the spectrum, mechanics, thermal, optical uniformity, and scattering loss of more than 1,000 YAG-based laser ceramics purchased from Konoshima. The research results show that the optical quality of small-sized YAG laser ceramics has reached the level of corresponding single crystals, while large-sized YAG laser ceramics are even better than single crystals in terms of doping concentration uniformity and optical uniformity. Laser ceramics have begun to be used in the field of high-energy lasers in the United States. Since 2009, based on the large-sized, high-quality Nd:YAG / Yb:YAG laser ceramic slabs provided by Konoshima, Japan, Marsh and Northrop Grumman have achieved 100kW and 105kW laser outputs respectively, fully demonstrating the application potential of laser ceramics in high-energy solid lasers. The research results show that by simply increasing the number of slats and increasing the aperture of the gain medium, the output power of the laser can be increased linearly, which provides a new solution for the technical approach of using large-aperture gain media and single resonant cavity to achieve high-power laser calibration amplification. One of its core technologies is high doping concentration uniformity and large-size laser ceramic gain media. The DiPOLE-100 laser developed by the Rutherford Appleton Laboratory in the UK in 2016 has been running stably for more than 1 hour at 100J and 10Hz, becoming a new milestone in the history of solid-state laser development. The laser head of the laser uses 6 pieces of Cr4+:YAG-edged Yb:YAG laser ceramics (120mm×120mm×8.5mm, 10mm wide) customized from Konoshima, Japan, which fully demonstrates the advantages of laser ceramics in gain medium design flexibility, large size, and high optical uniformity.
[0004] In 2018, LLNL made new progress in the design and preparation of laser ceramics. Starting from spray pyrolysis of YAG powder, they publicly reported the first additively formed Nd:YAG laser ceramics in the world through slurry direct writing technology, achieving high interface control accuracy, simple configuration of composite structure preparation, and obtaining a peak power of 2.27kW laser output. This has explored a new technical path for people to start from the performance requirements of lasers, artificially design laser gain medium structures, and achieve controllable preparation.
[0005] my country has been conducting research on laser ceramics since 2001. The Shanghai Institute of Ceramics, Chinese Academy of Sciences, first achieved laser output in 2006 and achieved high-efficiency laser output with a power of 4350W in 2013. The scattering loss of the laser ceramic slabs used was at the level of 0.002-0.003cm-1. In October 2016, the Shanghai Institute of Ceramics, Chinese Academy of Sciences, prepared a gradient-doped YAG / Nd:YAG / YAG composite laser ceramic slab (five-segment) with a size of 150.2mm×30mm×2.5mm. The scattering loss was less than 0.001cm-1, and a single slab had a maximum laser output of 7088W, fully demonstrating the advantages of gradient-doped composite laser ceramics in power extraction. In 2021, Wei Meng'en and others from the Hefei Institute of Physical Science, Chinese Academy of Sciences used 0.39-0.80at.% gradient-doped Nd:YAG rod-shaped crystals as gain media and obtained 24.2W, 2kHz 1064nm laser output, confirming that the use of gradient-doped crystals can significantly homogenize the thermal distribution of the pump light in the propagation direction inside the rod-shaped crystal, greatly reducing the temperature gradient and thermal lens effect inside the crystal, and significantly improving the output power and light extraction efficiency of the laser.
[0006] For multi-segment gradient-doped neodymium ion laser gain media, composite structure laser ceramics have greater application potential. Not only do they have a short processing cycle and low processing cost, but through careful design and preparation, they can not only greatly homogenize the temperature distribution inside the gain medium, improve the light extraction efficiency and output power, but also suppress the parasitic oscillation problem that is prone to occur in all-solid-state amplifiers and reduce the intensity noise of the laser. In addition, the flexible doping and low-cost preparation characteristics of laser ceramics themselves are more conducive to experimental research on more suitable Cr ion doping concentrations and improve the laser's adaptability to the space environment.
[0007] The characteristics of composite structure laser ceramics are flexible design and short preparation cycle. However, since the composite structure is destined to be accompanied by strong interface effects (the uniformity of stress, gain ion doping, etc. will deteriorate to a certain extent), although the interface effect can be controlled at a low level through process control, the process parameters will also change accordingly due to different composite structure design schemes. Therefore, it is of great significance to formulate testing methods for ceramic laser output characteristics based on the characteristics of composite structure laser ceramics.
[0008] The authorized invention patent "Measurement device, measurement method and application for measuring weak anisotropy in large-scale isotropic laser media (ZL 202111619346.6)" mainly solves the problem of measuring weak anisotropy caused by various factors in isotropic laser media by building a laser device and measuring the power, polarization and other characteristics of the output laser. "Multilayer YAG-Tm: YAG-YAG-Ho: YAG-YAG composite laser ceramics and their preparation method and application (ZL201410478024.8)" not only proposes the preparation method of multi-type gain ion doped composite structure laser ceramics, but also mentions the measurement of the linear transmittance and fluorescence characteristics of the sample, but does not involve the comprehensive performance test of ceramic samples. "Composite laser ceramics and their preparation method (ZL 201410648103.9)" mainly proposes a method for the processing and preparation of composite structure laser ceramics composed of lamellar chromium-doped lutetium aluminum garnet (Cr:LuAG) ceramics and lamellar neodymium-doped lutetium aluminum garnet (Nd:LuAG) ceramics stacked on top of each other and wrapped with samarium-doped lutetium aluminum garnet (Sm:LuAG) ceramics. The main purpose is to improve the pump coupling efficiency and fluorescence lifetime. The patent does not involve the performance test of composite structure laser ceramics. The accepted invention patent "A design method for a gradient-doped composite structure laser ceramic (202310193801.3)" mainly proposes a gradient-doped composite structure laser ceramic design method for the traditional uniformly doped gain medium due to the exponential attenuation characteristics of the pump light along the transmission direction and the thermal gradient characteristics along the vertical optical path transmission direction. The serious non-uniformity of the temperature difference and stress difference inside the crystal caused by the e-exponential attenuation characteristics of the pump light along the transmission direction and the thermal gradient characteristics along the vertical optical path transmission direction. The performance test of the prepared composite structure laser ceramics is not involved.
[0009] Therefore, there is an urgent need to design a method to test the performance of composite structure laser ceramics. Summary of the invention
[0010] In order to solve the technical problems existing in the above-mentioned prior art, the purpose of the present invention is to provide a performance testing method for composite structure laser ceramics, to realize the performance testing of composite structure laser ceramics, and to provide strong support for the preparation of high-performance composite structure laser ceramics.
[0011] To achieve the above-mentioned purpose, the present invention provides a performance testing method for composite structure laser ceramics, including physical and chemical property testing and laser output property testing of composite structure laser ceramics;
[0012] The physical and chemical property test at least includes: ceramic density test, microstructure test, transmittance test, stress test, and ion doping test;
[0013] The laser output characteristic test at least includes: pump light absorption characteristic test, thermal lens focal length test, end surface temperature test, and laser output power test.
[0014] According to a technical solution of the present invention, the pump light absorption characteristic test is completed by building a pump laser absorption test optical path based on a composite structure laser ceramic. The specific process is as follows:
[0015] The pump light absorption characteristics of the composite laser ceramics were evaluated by measuring the pump light absorption efficiency under two conditions: with and without laser output, and comparing it with the theoretical absorption efficiency of the pump light.
[0016] The pump laser is irradiated on different positions of the composite structure laser ceramic, and the pump light absorption uniformity of the composite structure laser ceramic is quantitatively evaluated by measuring the pump light absorption characteristics of different areas of the composite structure laser ceramic.
[0017] According to a technical solution of the present invention, the pump light absorption efficiency is calculated using the following formula:
[0018]
[0019] Among them, P1 is the coupled pump light power, P1 is the residual pump light power, α is the absorption coefficient of the composite structure laser ceramic, and l is the length of the composite structure laser ceramic.
[0020] According to a technical solution of the present invention, by measuring the thermal lens focal length of the composite structure laser ceramic under different power conditions and comparing it with the theoretical calculated value, the improvement of the thermal effect of the composite structure laser ceramic is evaluated;
[0021] Among them, the theoretical calculated value of the focal length of the thermal lens is f th-c The calculation is done by the following formula:
[0022]
[0023] Among them, k c is the thermal conductivity, ω p is the spot radius of the pumping light, dn / dt is the thermo-optic coefficient, α is the absorption coefficient of the laser medium, l is the length of the medium, P in is the pump laser power acting on the composite structure laser ceramic, η abd is the absorption rate of the medium to the pump laser, η b The conversion rate of absorbed energy into heat.
[0024] According to a technical solution of the present invention, the focal length of the thermal lens is measured by constructing a Mach-Zehnder interferometer to measure the movement of interference fringes before and after the pump laser is loaded, and the optical path difference before and after the pump light is loaded is determined to complete the measurement of the focal length of the thermal lens. The specific formula is expressed as follows:
[0025]
[0026] Among them, f th-t is the measured value of the focal length of the thermal lens, Δm is the change in interference fringes, λ is the wavelength of the interferometer laser detection, r0 is the end face radius of the composite structure laser ceramic, and n0 is the refractive index of the composite structure laser ceramic.
[0027] According to a technical solution of the present invention, a laser is built using a composite structure laser ceramic and laser output is achieved. Under different pump power conditions, the temperature of the front and rear end faces of the composite structure laser ceramic is measured to evaluate the improvement of the temperature distribution gradient by the composite structure laser ceramic and complete the end face temperature test.
[0028] According to a technical solution of the present invention, the laser output power test is used to comprehensively evaluate the performance of composite structure laser ceramics, build a laser using composite structure laser ceramics, and realize laser output, and measure the laser output power under different pump powers.
[0029] According to a technical solution of the present invention, the process of the ceramic density test includes: measuring the actual density of the composite structure laser ceramic and comparing it with the theoretical density value to preliminarily evaluate whether there are a large number of bubbles inside the composite structure laser ceramic sample;
[0030] The process of the microstructure test includes: observing the internal grains, grain boundaries and miscellaneous items of the composite structure laser ceramics to qualitatively evaluate whether the interface characteristics of the composite structure laser ceramics meet the laser working requirements;
[0031] The transmittance test process includes: measuring the actual transmittance of the composite structure laser ceramics to quantitatively evaluate the uniformity and loss of the composite structure laser ceramics;
[0032] The stress test process includes: measuring the stress of the composite structure laser ceramic, observing the stress of the corners and interfaces of the composite structure laser ceramic sample, avoiding the large stress abnormal area of the composite structure laser ceramic, and ensuring that the composite structure laser ceramic used for laser output has a relatively uniform stress characteristic;
[0033] The process of the ion doping test includes: testing the gain ion doping concentration of the composite structure laser ceramic sample to preliminarily evaluate the pump light absorption and gain of the composite structure laser ceramic.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] The present invention proposes a performance testing method for composite structure laser ceramics. By conducting comprehensive performance tests on the microstructure, doping uniformity, pump light absorption characteristics, pump light absorption uniformity and other aspects of the composite structure ceramics that are related to the internal structure and laser output characteristics of the laser ceramics, strong support can be provided for the preparation of high-performance composite structure laser ceramics.
[0036] By establishing a complete test method for composite laser ceramics, the performance of the laser gain medium of composite laser ceramics can be effectively evaluated, thereby providing an effective test method for the flexible design, low-cost preparation and rapid application of composite laser ceramics in high-performance lasers. Furthermore, in the sample trial production stage, the design and development effects of composite laser ceramics can be effectively evaluated, and reliable test data can be provided for design optimization and process optimization; at the same time, in the mass production stage of products, reliable and rapid performance evaluation can be achieved, production efficiency can be improved, and development costs can be reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0038] Figure 1 A schematic diagram of a performance test flow chart of a composite structure laser ceramic in an embodiment of the present invention;
[0039] Figure 2 A schematic diagram of a composite structure laser ceramic pump light absorption characteristic testing device according to an embodiment of the present invention;
[0040] Figure 3 A schematic diagram of a focal length testing device for a composite structure laser ceramic thermal lens according to an embodiment of the present invention;
[0041] Figure 4 A schematic diagram shows a device for testing laser output and temperature characteristics of composite structure laser ceramics according to an embodiment of the present invention. DETAILED DESCRIPTION
[0042] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] like Figures 1 to 4 As shown, a performance testing method of a composite structure laser ceramic of the present invention includes a physical and chemical property test and a laser output property test of the composite structure laser ceramic.
[0044] The physical and chemical property test at least includes: ceramic density test 101 , microstructure test 102 , transmittance test 103 , stress test 104 , and ion doping test 105 .
[0045] The ceramic density test mainly measures the actual density of the composite structure laser ceramics and compares it with the theoretical density value to preliminarily evaluate whether there are a large number of bubbles inside the composite structure laser ceramic sample.
[0046] Microstructure testing is mainly used to qualitatively evaluate whether the interface characteristics of composite laser ceramics meet the laser working requirements by observing the internal grains, grain boundaries, and miscellaneous items of composite laser ceramics.
[0047] The transmittance test is mainly used to quantitatively evaluate the uniformity and loss of composite structure laser ceramics by measuring the actual transmittance of composite structure laser ceramics.
[0048] The stress test mainly measures the stress conditions of composite structure laser ceramics, focusing on observing the stress conditions at the corners and interfaces of composite structure laser ceramic samples, in order to avoid areas with large stress anomalies in composite structure laser ceramics and ensure that the composite structure laser ceramics used for laser output have relatively uniform stress characteristics.
[0049] The ion doping test is mainly used to preliminarily evaluate the pump light absorption and gain of the composite structure laser ceramics by testing the gain ion doping concentration of the composite structure laser ceramic samples.
[0050] The laser output characteristic test at least includes: a pump light absorption characteristic test 106 , a thermal lens focal length test 107 , an end surface temperature test 108 , and a laser output power test 109 .
[0051] The pump light absorption characteristic test is mainly carried out by building a pump laser absorption test optical path based on composite structure laser ceramics, as shown in the attached figure. Figure 2 As shown, Figure 2The invention discloses a pump light absorption characteristic test device for composite structure laser ceramics, comprising: a pump light source 201, a scanning device 202, a shaping block 203, an input cavity mirror 204, a composite structure laser ceramic 205, an output cavity mirror 206, a filter device 207 and a power meter 208, and performs a pump light absorption characteristic test for composite structure laser ceramics in three modes. The first mode is a pump light absorption characteristic test in a laser output mode, wherein the laser resonant cavity is adjusted to make it run stably and the output power reaches a maximum value, the output laser is filtered out by a "filter device 207", the remaining pump laser power is measured by a power meter and compared with the total pump power acting on the composite structure laser ceramics, and the absorption efficiency of the composite structure laser ceramics is obtained. The second mode is a pump light absorption characteristic test in a non-laser output mode, wherein the "output cavity mirror 206" and the "filter device 207" are removed on the basis of the first mode, the remaining pump laser power is measured by a power meter and compared with the total pump power acting on the composite structure laser ceramics, and the absorption efficiency of the composite structure laser ceramics is obtained. The third mode is based on the second mode, using the "scanning device 202" to change the position of the pump source laser in the composite structure laser ceramic to test the pump light absorption characteristics of different areas of the composite structure laser ceramic.
[0052] The pump light absorption characteristics of the composite structure laser ceramics were evaluated by measuring the pump light absorption efficiency with and without laser output in the first mode and the second mode respectively, and comparing it with the theoretical absorption efficiency of the pump light.
[0053] Furthermore, in the third mode, the pump laser is irradiated on different positions of the composite structure laser ceramic, and the pump light absorption uniformity of the composite structure laser ceramic is quantitatively evaluated by measuring the pump light absorption characteristics of different areas of the composite structure laser ceramic.
[0054] The pump light absorption efficiency is calculated using the following formula:
[0055]
[0056] Among them, P1 is the coupled pump light power, P1 is the residual pump light power, α is the absorption coefficient of the composite structure laser ceramic, and l is the length of the composite structure laser ceramic.
[0057] The thermal lens focal length test mainly measures the thermal lens focal length of the composite structure laser ceramic under different power conditions and compares it with the theoretical calculated value to evaluate the improvement of the thermal effect of the composite structure laser ceramic. The theoretical calculated value is shown in (2). The test device is shown in the attached figure. Figure 3 As shown, Figure 3The figure shows a focal length test device of a composite structure laser ceramic thermal lens, including: a detection laser source 301, a detection light shaping module 302, a first reflector 304, a composite structure laser ceramic 305, a beam combining mirror 306, a second reflector 307, an optical lens 308, a shaping module 309, a pump light shaping module 310 and a pump laser source 311.
[0058] Among them, the detection laser source 301, the detection light shaping module 302, the first reflector 304, the composite structure laser ceramic 305, the beam combiner 306, the second reflector 307, the optical lens 308 and the shaping module 309 constitute a Mach-Zehnder interferometer containing the composite structure laser ceramic. The pump light shaping module 310 and the pump laser source 311 jointly realize the coupling of the pump laser into the composite structure laser ceramic. The changes of the interference fringes with and without the pump light are collected through the optical lens 308 and the shaping module 309, the changes of the optical path difference are calculated, and the thermal lens focal length of the composite structure laser ceramic under different pump powers is calculated.
[0059] The focal length of the thermal lens is measured by constructing a Mach-Zehnder interferometer to measure the movement of interference fringes before and after the pump laser is loaded, thereby determining the optical path difference before and after the pump light is loaded, thereby achieving the measurement of the focal length of the thermal lens.
[0060] Among them, the theoretical calculated value of the focal length of the thermal lens is f th-c The calculation is done by the following formula:
[0061]
[0062] Among them, k c is the thermal conductivity, ω p is the spot radius of the pumping light, dn / dt is the thermo-optic coefficient, α is the absorption coefficient of the laser medium, l is the length of the medium, P in is the pump laser power acting on the composite structure laser ceramic, η abs is the absorption rate of the medium to the pump laser, η b The conversion rate of absorbed energy into heat.
[0063] The measured value of the focal length of the thermal lens is f th-c The calculation is done by the following formula:
[0064]
[0065] Among them, f th-t is the measured value of the focal length of the thermal lens, Δm is the change in interference fringes, λ is the wavelength of the interferometer laser detection, r0 is the end face radius of the composite structure laser ceramic, and n0 is the refractive index of the composite structure laser ceramic.
[0066] Attached Figure 4The figure shows a composite structure laser ceramic laser output and temperature characteristic testing device, including a pump laser source 401, a shaping module 402, an input cavity mirror 403, a temperature detection module 404, a composite structure laser ceramic 405, an output cavity mirror 406, a filter device 407 and a power meter 408.
[0067] The temperature detection module 404 is a composite structure laser ceramic end surface temperature testing device.
[0068] A laser is built using composite structure laser ceramics and laser output is achieved. Under different pump power conditions, the temperature of the front and rear end faces of the composite structure laser ceramics is measured to evaluate the improvement of the temperature distribution gradient by the composite structure laser ceramics and complete the end face temperature test.
[0069] The laser output power test is used to comprehensively evaluate the performance of composite structure laser ceramics, build a laser using composite structure laser ceramics, achieve laser output, and measure the laser output power under different pump powers.
[0070] The present invention provides a performance testing method for composite structure laser ceramics, including physical and chemical property testing and laser output property testing of composite structure laser ceramics; the physical and chemical property testing at least includes: ceramic density testing, microstructure testing, transmittance testing, stress testing, and ion doping testing; the laser output property testing at least includes: pump light absorption property testing, thermal lens focal length testing, end surface temperature testing, and laser output power testing. The present invention, by testing the internal structural properties and laser output properties of composite structure laser ceramics, realizes the evaluation of the comprehensive performance of laser ceramics, and provides rapid optimization feedback for the design and preparation of composite structure laser ceramics.
[0071] It should be noted that the above is a preferred embodiment of the present invention. It should be pointed out that although the preferred embodiment of the present invention has been described, once the basic creative concept of the present invention is known, a number of improvements and modifications can be made by a person skilled in the art without departing from the principles of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention. Therefore, the attached claims are intended to be interpreted as including the preferred embodiment and all changes and modifications that fall within the scope of the embodiments of the present invention.
Claims
1. A performance testing method for composite structure laser ceramics, characterized in that: Including physical and chemical properties test and laser output characteristics test of composite structure laser ceramics; The physical and chemical property test at least includes: ceramic density test, microstructure test, transmittance test, stress test, and ion doping test; The laser output characteristic test at least includes: pump light absorption characteristic test, thermal lens focal length test, end surface temperature test, and laser output power test.
2. The performance testing method of composite structure laser ceramics according to claim 1, characterized in that: The pump light absorption characteristic test is completed by building a pump laser absorption test optical path based on composite structure laser ceramics. The specific process is as follows: The pump light absorption characteristics of the composite laser ceramics were evaluated by measuring the pump light absorption efficiency under two conditions: with and without laser output, and comparing it with the theoretical absorption efficiency of the pump light. The pump laser is irradiated on different positions of the composite structure laser ceramic, and the pump light absorption uniformity of the composite structure laser ceramic is quantitatively evaluated by measuring the pump light absorption characteristics of different areas of the composite structure laser ceramic.
3. The performance testing method of composite structure laser ceramics according to claim 2 is characterized in that: The pump light absorption efficiency is calculated using the following formula: Among them, P1 is the coupled pump light power, P1 is the residual pump light power, α is the absorption coefficient of the composite structure laser ceramic, and l is the length of the composite structure laser ceramic.
4. The performance testing method of composite structure laser ceramics according to claim 1, characterized in that: By measuring the thermal lens focal length of the composite structure laser ceramics under different power conditions and comparing it with the theoretical calculated value, the improvement of the thermal effect of the composite structure laser ceramics is evaluated; Among them, the theoretical calculated value of the focal length of the thermal lens is f th-c The calculation is done by the following formula: Among them, k c is the thermal conductivity, ω p is the spot radius of the pumping light, dn / dt is the thermo-optic coefficient, α is the absorption coefficient of the laser medium, l is the length of the medium, P in is the pump laser power acting on the composite structure laser ceramic, η abs is the absorption rate of the medium to the pump laser, η b The conversion rate of absorbed energy into heat.
5. The performance testing method of composite structure laser ceramics according to claim 4 is characterized in that: The focal length of the thermal lens is measured by constructing a Mach-Zehnder interferometer to measure the movement of interference fringes before and after the pump laser is loaded, and the optical path difference before and after the pump light is loaded is determined to complete the measurement of the focal length of the thermal lens. The specific formula is expressed as: Among them, f th-t is the measured value of the focal length of the thermal lens, Δm is the change in interference fringes, λ is the wavelength of the interferometer laser detection, r0 is the end face radius of the composite structure laser ceramic, and n0 is the refractive index of the composite structure laser ceramic.
6. The performance testing method of composite structure laser ceramics according to claim 1 is characterized in that: A laser is built using composite structure laser ceramics and laser output is achieved. Under different pump power conditions, the temperature of the front and rear end faces of the composite structure laser ceramics is measured to evaluate the improvement of the temperature distribution gradient by the composite structure laser ceramics and complete the end face temperature test.
7. The performance testing method of composite structure laser ceramics according to claim 6 is characterized in that: The laser output power test is used to comprehensively evaluate the performance of composite structure laser ceramics, build a laser using composite structure laser ceramics, achieve laser output, and measure the laser output power under different pump powers.
8. The performance testing method of composite structure laser ceramics according to claim 1 is characterized in that: The ceramic density test process includes: measuring the actual density of the composite structure laser ceramic and comparing it with the theoretical density value to preliminarily evaluate whether there are a large number of bubbles inside the composite structure laser ceramic sample; The process of the microstructure test includes: observing the internal grains, grain boundaries and miscellaneous items of the composite structure laser ceramics to qualitatively evaluate whether the interface characteristics of the composite structure laser ceramics meet the laser working requirements; The transmittance test process includes: measuring the actual transmittance of the composite structure laser ceramics to quantitatively evaluate the uniformity and loss of the composite structure laser ceramics; The stress test process includes: measuring the stress of the composite structure laser ceramic, observing the stress of the corners and interfaces of the composite structure laser ceramic sample, avoiding the large stress abnormal area of the composite structure laser ceramic, and ensuring that the composite structure laser ceramic used for laser output has a relatively uniform stress characteristic; The process of the ion doping test includes: testing the gain ion doping concentration of the composite structure laser ceramic sample to preliminarily evaluate the pump light absorption and gain of the composite structure laser ceramic.
Citation Information
Patent Citations
Multilayer yag-tm:yag-yag-ho:yag-yag composite laser ceramics and its preparation method and application
CN104261831B
Measurement apparatus, measurement method and application for measuring weak anisotropy in large-size isotropic laser media.
CN114384068B
Highly doped Yb, Er: YAG transparent ceramic and manufacturing method thereof
CN101851096A
Composite laser ceramic and preparation method thereof
CN104446430A
Design method of gradient doped composite structure laser ceramic
CN116415420A
Cited By
Foaming ceramic plate performance analysis method and device
CN120495290A